E- government and innovation in Italian Public Administration: A business approach (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
E-Government consists of a strategic instrument for re-formulating the organization and the operation of Public Administrations, acting as a catalyst of trends and changes. It not only represents a resource that allows economic and operational advantages to be obtained, but is also an instrument that is capable of modifying the pre-existing operational mechanisms of the organization, guaranteeing a fast adaptation to continuous changes in the external environment. The use of e-Government not only facilitates the internal activities of the Public Administration, but also has the advantage of facilitating the relationship between different administrations, as well as the interaction with citizens and with businesses. The impact that e-Government can have is that of a better Public Administration, in that it allows public policies to be optimized, the quality of services to be raised, the involvement of the citizens to be widened, and other specific fundamental activities to be improved.The present work intends to illustrate the comprehensive framework of the public administration system in Italy and of the main tendencies in progress, paying particular attention to the development of new management logic, considering e-Government not only as a merely technological phenomenon, but also analyzing it in its full meaning with regards to the process of change and modernization of the public administration.